Food toxicology and forensics (Academic Press, 2021)
Food Toxicology and Forensics presents an overview on these subjects, along with the analytical tools necessary to handle the complexity of the issues at play between them. The book discusses the presence of foreign substances in food despite forensic analysis and supports the scientific community, laboratories and regulatory bodies in their aim to identify food fraud. Topics include the forensic attribution profiling of food by liquid chromatography (LC), contemporary mass spectrometry (MS), tandem mass spectrometry (MS/MS) and liquid chromatography coupled to mass spectrometry (LC-MS), the application of ambient ionization mass spectrometry (AIMS) techniques for the analysis of food samples, and more.